Education for Citizenship in the curriculum of the LOE - Bolivar Botía, Antonio (Avances en Supervisión Educativa, 2008)
Citizenship education, well understood, is not task only of a subject. Besides, it understands the key competences and, particularly, the civic and social competence; is task of whole school and, beyond, corresponds to the community. The paper describes these four dimensions (subject, key competences, vhole school, community).